The development of interpersonal relationship in family structures - İlaha Dilkhosh Hajiyeva (Research Retrieval and Academic Letters, 2025)
Concepts such as marital relationship, marital satisfaction, marital happiness and marital harmony have formed the basis of many studies. Not only psychiatrists and psychologists, but also many scientists from different branches of science are interested in the subject. Many studies are conducted based on these concepts within the framework of different areas of expertise. Many definitions have been used by social scientists on how a marriage can function well. In general, marriage is evaluated in two simple ways: The first term is the concept of marital continuity, which includes issues such as annulment, divorce, separation, abandonment. A permanent marriage ends with the natural death of one of the spouses. An unstable marriage ends with the will of one or both spouses. Another term is the concept of marital quality if the marriage continues. This concept is directly related to how the marital relationship is during the marriage, how the spouses feel about this and how they are affected by this situation.